2006
DOI: 10.1038/sj.onc.1209083
|View full text |Cite
|
Sign up to set email alerts
|

A crucial function of PDGF in TGF-β-mediated cancer progression of hepatocytes

Abstract: Polarized hepatocytes expressing hyperactive Ha-Ras adopt an invasive and metastatic phenotype in cooperation with transforming growth factor (TGF)-b. This dramatic increase in malignancy is displayed by an epithelial to mesenchymal transition (EMT), which mimics the TGFb-mediated progression of human hepatocellular carcinomas. In culture, hepatocellular EMT occurs highly synchronously, facilitating the analysis of molecular events underlying the various stages of this process. Here, we show that in response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
177
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(185 citation statements)
references
References 104 publications
6
177
1
1
Order By: Relevance
“…It has been observed that STAT3 can also regulate the expression of other angiogenic molecules, such as basic FGF (bFGF) [133] which participates in angiogenesis by inducing the migration, proliferation, and differentiation of endothelial cells and by regulating VEGF expression in tumor cells in an autocrine and paracrine fashion [240]. It is widely believed that the ability of PDGFs to induce liver fibrosis and neoplastic cell transformation is closely associated with the transcriptional induction of TGFβ, an essential mediator of fibrogenesis [241,242]. TGFβ and PDGFs act through activation of STAT3 [75,76] leading to the upregulation of genes promoting cell proliferation, survival, and cell transformation [77].…”
Section: Role Of Stat3 In Angiogenesismentioning
confidence: 99%
“…It has been observed that STAT3 can also regulate the expression of other angiogenic molecules, such as basic FGF (bFGF) [133] which participates in angiogenesis by inducing the migration, proliferation, and differentiation of endothelial cells and by regulating VEGF expression in tumor cells in an autocrine and paracrine fashion [240]. It is widely believed that the ability of PDGFs to induce liver fibrosis and neoplastic cell transformation is closely associated with the transcriptional induction of TGFβ, an essential mediator of fibrogenesis [241,242]. TGFβ and PDGFs act through activation of STAT3 [75,76] leading to the upregulation of genes promoting cell proliferation, survival, and cell transformation [77].…”
Section: Role Of Stat3 In Angiogenesismentioning
confidence: 99%
“…Important molecular pathway involved in EMT are Wnt/betacatenin signaling [95,96] and through growth factor signalling like PDGF [97] .…”
Section: Hepatocarcinogenesis and Tumormicroenviromentmentioning
confidence: 99%
“…58 In the context of cancer-related EMT, all 3 TGFb isoforms can induce hepatocarcinoma EMT that is mediated by downstream induction and signaling of the platelet derived growth factor (PDGF) A. 59 In EMT and metastatic spreading of breast cancer with oncogenic phosphatidylinositol 3' kinase (PI3K)/Akt pathway activation, TGFb2 activity is required; Akt directly phosphorylates Twist1, causing its stabilization and transcriptional activation, and leading to the enhanced expression of the TGFb2 gene. 60 Finally, EMT and MET cycles are controlled by the reciprocal loop between TGFb and members of the miR-200 family.…”
Section: Introductionmentioning
confidence: 99%